PENGARUH MODEL PEMBELAJARAN DRAGON BALL TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN IPA DI KELAS V MI - Hajar Basri; Misrina; Yusra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to investigate the impact of the Dragon Ball teaching model on students' critical thinking skills in science subjects in grade V of MIN 3 Lhokseumawe City. The methodology used is a quantitative approach with a quasi-experimental design and pretest-posttest in the control group. The sample consisted of two classes, namely an experimental class using the Dragon Ball learning model and a control class applying the Problem Based Learning (PBL) model, each with 31 students. Data were obtained through critical thinking ability tests conducted before the lesson (pretest) and after the lesson (posttest). The research instrument has been validated by experts to ensure that the tool is suitable for use. Data analysis was carried out using descriptive and inferential statistics. Before the analysis, prerequisite tests were carried out including normality and homogeneity tests, while hypothesis testing used the Independent Sample t-Test. The results of the descriptive analysis showed that the average posttest score for the experimental class was 78.23, higher than the control class which reached 62.54. The normality test showed that the data from both classes were normally distributed, while the homogeneity test showed homogeneous variance. The results of the hypothesis testing showed a significant difference in critical thinking skills between students who used the Dragon Ball learning model and those who learned with the Problem Based Learning model. Thus, it can be concluded that the Dragon Ball learning model has a positive impact on students' critical thinking skills in science learning in class V MIN 3 Lhokseumawe City.